Biomass hard carbon surface optimization method and application thereof in sodium ion battery

By optimizing the surface treatment of biomass hard carbon materials, coated with dopamine hydrochloride and carbonized at high temperature, the problem of low efficiency and poor rate performance of hard carbon anode in sodium ion batteries is solved, and efficient and stable sodium ion battery performance is achieved.

CN119637851APending Publication Date: 2025-03-18BEIJING INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510117403.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The first time the existing hard carbon anode in sodium ion batteries is low in efficiency and poor in rate performance, making it difficult to meet commercial needs.

Method used

By preoxidizing the biomass raw material under an air atmosphere and carbonizing at high temperature under an inert atmosphere, a preliminary carbonized powder is obtained, and reacted with dopamine hydrochloride in a buffer solution to form a polydopamine-coated hard carbon powder, and then carbonized at high temperature to prepare an optimized biomass hard carbon material.

Benefits of technology

It improves the first Coulomb efficiency, reversible specific capacity and rate performance of biomass hard carbon materials, enhances cycling stability, and meets the commercial needs of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637851A_ABST
    Figure CN119637851A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass hard carbon surface optimization method and application of the biomass hard carbon surface optimization method in a sodium-ion battery, and belongs to the technical field of sodium-ion batteries. The biomass hard carbon surface optimization method comprises the following steps: pre-oxidizing a biomass raw material, and carrying out high-temperature carbonization in an inert atmosphere to obtain primary carbonized powder; dispersing the preliminarily carbonized powder and dopamine hydrochloride in a buffer solution, and reacting to obtain hard carbon powder coated with polydopamine; and carrying out high-temperature carbonization on the hard carbon powder coated with the polydopamine in an inert atmosphere to obtain the biomass hard carbon. The biomass hard carbon prepared by the invention has high first coulombic efficiency, high reversible specific capacity, excellent rate capability and good cycle stability, and can overcome the problems of low first coulombic efficiency and poor rate capability of the existing hard carbon negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a biomass hard carbon surface optimization method and application thereof in sodium ion batteries. Background Art

[0002] Hard carbon refers to a type of carbon that is difficult to graphitize above 2500°C and is a type of amorphous carbon. Hard carbon can be divided into biomass-based hard carbon and organic polymer-based hard carbon. The former is obtained by heat treatment of biomass, and the latter is obtained by artificial synthesis. Hard carbon has a spherical, linear or porous morphology. Compared with graphite (0.335nm), the distorted carbon layer structure of hard carbon increases the repulsive force between graphitized carbon layers, resulting in a larger interlayer spacing (0.38nm). This large interlayer spacing and nanopores are conducive to the diffusion of ions and the stability of the structure during the circulation process.

[0003] Biomass hard carbon is inexpensive, widely available, and can usually maintain the morphology of the precursor during the material synthesis process. However, the current hard carbon negative electrodes generally face problems such as low first coulombic efficiency and poor rate performance in the actual application of sodium-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a biomass hard carbon surface optimization method and its application in sodium ion batteries to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a method for preparing biomass hard carbon, comprising the following steps:

[0007] (1) pre-oxidizing the biomass raw material in an air atmosphere and then carbonizing it at a high temperature in an inert atmosphere to obtain a preliminary carbonized powder;

[0008] (2) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution to obtain a polydopamine-coated hard carbon powder after reaction;

[0009] (3) Carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain the biomass hard carbon.

[0010] Furthermore, in step (1): the pre-oxidation temperature is 200-500° C., and the holding time is 2-10 h; the high-temperature carbonization temperature is 1300-1500° C., and the holding time is 2-4 h; and the inert atmosphere is a nitrogen atmosphere.

[0011] Furthermore, in step (2): the mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:1.

[0012] Furthermore, in step (3): the temperature of the high temperature carbonization is 900-1100° C., and the time is 2-4 hours; and the inert atmosphere is a nitrogen atmosphere.

[0013] Furthermore, the method for preparing biomass hard carbon further comprises: before the pre-oxidation in step (1), crushing the biomass raw material, washing and drying it to obtain a biomass precursor;

[0014] The biomass raw materials are willow branches, peach branches, willow branches, crape myrtle branches, cherry branches or plum branches.

[0015] Furthermore, in step (2): the reaction time is 24 hours; and the buffer solution is Tris buffer.

[0016] The biomass precursor has a typical hierarchical porous structure, including micropores, mesopores and macropores. After carbonization, the layered pore structure can be retained. + The storage of ions provides active sites to obtain a high specific capacity hard carbon negative electrode.

[0017] The present invention uses biomass precursors such as willow branches, peach branches, red willow branches, tamarisk branches, crape myrtle branches, camellia branches, cherry branches or plum branches as raw materials, and prepares biomass hard carbon materials through surface optimization, which can improve the first coulomb efficiency of the hard carbon material and reduce irreversible sodium ion loss, thereby meeting the commercialization needs of sodium ion batteries.

[0018] The second technical solution of the present invention: a biomass hard carbon prepared by the above preparation method.

[0019] The third technical solution of the present invention: an application of the above-mentioned biomass hard carbon in the preparation of negative electrode of sodium ion battery.

[0020] Technical solution four of the present invention: a sodium ion battery negative electrode, comprising the above-mentioned biomass hard carbon.

[0021] Furthermore, the method for preparing the negative electrode of the sodium ion battery comprises:

[0022] The biomass-based hard carbon and sodium alginate are dissolved in water at a mass ratio of 9:1 to obtain a biomass-based hard carbon electrode slurry; the electrode slurry is applied on an aluminum current collector, and after drying, it is punched on a tablet press to obtain a sodium ion battery negative electrode.

[0023] Technical solution 5 of the present invention: A method for optimizing the surface of biomass hard carbon, comprising the following steps:

[0024] (1) pre-oxidizing the biomass raw material in an air atmosphere and then carbonizing it at a high temperature in an inert atmosphere to obtain a preliminary carbonized powder;

[0025] (2) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution to obtain a polydopamine-coated hard carbon powder after reaction;

[0026] (3) Carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain the biomass hard carbon.

[0027] Furthermore, in step (1): the pre-oxidation temperature is 200 to 500° C., and the holding time is 2 to 10 hours;

[0028] Step (1): the temperature of the high temperature carbonization is 1300-1500° C., and the time is 2-4 hours; the inert atmosphere is a nitrogen atmosphere;

[0029] Step (2): the mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:1;

[0030] In step (3), the high temperature carbonization temperature is 900-1100° C., and the time is 2-4 hours; and the inert atmosphere is a nitrogen atmosphere.

[0031] Furthermore, the biomass hard carbon surface optimization method further includes: before the pre-oxidation in step (1), the biomass raw material is crushed, washed and dried to obtain a biomass precursor;

[0032] The biomass precursor is willow branch, peach branch, willow branch, crape myrtle branch, cherry branch or plum branch.

[0033] Furthermore, in step (2), the reaction time is 24 hours; and the buffer solution is Tris buffer.

[0034] The biomass hard carbon surface optimization method of the present invention can reduce the defects of the biomass hard carbon surface, optimize the functional groups of the biomass hard carbon surface, and can effectively solve the problems of low first coulombic efficiency and poor rate performance of the hard carbon negative electrode in the prior art.

[0035] The present invention discloses the following technical effects:

[0036] (1) The biomass hard carbon prepared by the present invention has high first coulombic efficiency, high reversible specific capacity, excellent rate performance and good cycle stability, which can overcome the problems of low first coulombic efficiency and poor rate performance of the existing hard carbon negative electrode.

[0037] (2) The biomass hard carbon of the present invention is prepared using biomass raw materials, which has the advantages of wide raw material sources and low prices. In addition, the structure of the biomass raw materials used in the present invention after carbonization is more suitable for use in sodium ion battery negative electrode materials, which can avoid the problem that the electrochemical performance of biomass-based hard carbon materials when used as sodium ion batteries is affected by their surface defects.

[0038] (3) The present invention uses polydopamine to repair the surface defects of hard carbon materials, optimizes the surface functional groups, and effectively reduces the side reactions between the electrode and the electrolyte, thereby obtaining a biomass hard carbon negative electrode material with high first coulombic efficiency, high reversible specific capacity and good cycle stability, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is a SEM image of the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0041] Figure 2 TEM image of the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0042] Figure 3 This is an XPS image of the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0043] Figure 4 This is a first cycle charge and discharge curve diagram of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0044] Figure 5 This is a rate performance diagram of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0045] Figure 6 This is a cycle performance diagram of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0047] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0051] In a first aspect, the present invention provides a method for preparing biomass hard carbon, comprising the following steps:

[0052] (1) crushing the biomass raw material, washing and drying it to obtain a biomass precursor;

[0053] The biomass raw materials are willow branches, peach branches, willow branches, crape myrtle branches, cherry branches or plum branches.

[0054] (2) pre-oxidizing the biomass raw material in an air atmosphere and then carbonizing it at a high temperature in an inert atmosphere to obtain a preliminary carbonized powder;

[0055] The temperature of pre-oxidation is 200-500°C, and the holding time is 2-10h; the temperature of high-temperature carbonization is 1300-1500°C, and the time is 2-4h; the inert atmosphere is nitrogen atmosphere.

[0056] (3) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution, and obtaining a polydopamine-coated hard carbon powder after reaction;

[0057] The mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:1;

[0058] The reaction time is 24 h; the buffer solution is Tris buffer.

[0059] (4) carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain biomass hard carbon;

[0060] The temperature of high temperature carbonization is 900-1100°C, and the time is 2-4 hours; the inert atmosphere is nitrogen atmosphere.

[0061] The second aspect of the present invention provides a biomass hard carbon prepared by the above preparation method.

[0062] The third aspect of the present invention provides an application of the above-mentioned biomass hard carbon in the preparation of negative electrodes for sodium ion batteries.

[0063] In a fourth aspect, the present invention provides a sodium ion battery negative electrode, comprising the above-mentioned biomass hard carbon.

[0064] In a specific embodiment of the present invention, a method for preparing a negative electrode of a sodium ion battery comprises:

[0065] Biomass-based hard carbon and sodium alginate are dissolved in water at a mass ratio of 9:1 to obtain a biomass-based hard carbon electrode slurry; the electrode slurry is applied on an aluminum current collector, dried, and then punched on a tablet press to obtain a sodium ion battery negative electrode.

[0066] In a fifth aspect, the present invention provides a method for optimizing the surface of biomass hard carbon, comprising the following steps:

[0067] (1) crushing the biomass raw material, washing and drying it to obtain a biomass precursor;

[0068] The biomass raw materials are willow branches, peach branches, willow branches, crape myrtle branches, cherry branches or plum branches.

[0069] (2) pre-oxidizing the biomass raw material in an air atmosphere and then carbonizing it at a high temperature in an inert atmosphere to obtain a preliminary carbonized powder;

[0070] The temperature of pre-oxidation is 200-500°C, and the holding time is 2-10h; the temperature of high-temperature carbonization is 1300-1500°C, and the time is 2-4h; the inert atmosphere is nitrogen atmosphere.

[0071] (3) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution, and obtaining a polydopamine-coated hard carbon powder after reaction;

[0072] The mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:1;

[0073] The reaction time is 24 h; the buffer solution is Tris buffer.

[0074] (4) carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain biomass hard carbon;

[0075] The temperature of high temperature carbonization is 900-1100°C, and the time is 2-4 hours; the inert atmosphere is nitrogen atmosphere.

[0076] Example 1

[0077] A biomass hard carbon surface optimization method:

[0078] (1) 5 g of peach branches were selected, crushed and sieved (200 mesh) in a grinder, washed and dried to obtain a biomass precursor.

[0079] (2) The biomass precursor was pre-oxidized in an air atmosphere (temperature of 300°C, holding time of 2h) to obtain a pre-oxidized sample.

[0080] (3) The pre-oxidized sample was subjected to high-temperature carbonization treatment under N2 atmosphere (carbonization temperature was 1300°C and holding time was 2 h) to obtain preliminary carbonized powder.

[0081] (4) 0.3 g of the preliminary carbonized powder and 0.05 g of dopamine hydrochloride (mass ratio of 6:1) were dispersed in 40 mL of Tris buffer, fully reacted for 24 h, filtered, washed and dried to obtain polydopamine-coated hard carbon powder.

[0082] (5) The polydopamine-coated hard carbon powder was subjected to high-temperature carbonization treatment (carbonization temperature was 900°C and insulation time was 2 h) under N2 atmosphere to obtain a surface-optimized biomass hard carbon material.

[0083] The SEM image of the surface optimized biomass hard carbon material prepared in Example 1 is shown in Figure 1 , TEM image see Figure 2 , XPS diagram Figure 3 ( Figure 3 HC in the figure is a sample without surface coating (the hard carbon material prepared in Comparative Example 1), and HC@C is a sample with surface coating (the biomass hard carbon material prepared in Example 1).

[0084] from Figures 1 to 3 It can be seen that the morphology of the biomass hard carbon material prepared in this embodiment is basically consistent with the morphology of the precursor. The TEM results show that the outermost layer is a surface coating layer with a thickness of about 15 nm. This ultra-thin carbon layer isolates the hard carbon from direct contact with the electrolyte, reduces the occurrence of side reactions, and thereby improves the first coulomb efficiency of the material. The XPS results show that the surface coating layer contains nitrogen doping, which is beneficial to accelerate the diffusion rate of sodium ions, thereby improving the rate performance.

[0085] Example 2

[0086] The same as Example 1, except that step (4) is specifically as follows: 0.4 g of the preliminary carbonized powder and 0.05 g of dopamine hydrochloride (mass ratio is 8:1) are dispersed in 40 mL of Tris buffer, fully reacted for 24 h, filtered, washed and dried to obtain a polydopamine-coated hard carbon powder.

[0087] Example 3

[0088] The same as Example 1, except that step (4) is specifically as follows: 0.5 g of the preliminary carbonized powder and 0.05 g of dopamine hydrochloride (mass ratio of 10:1) are dispersed in 40 mL of Tris buffer, fully reacted for 24 h, filtered, washed and dried to obtain a polydopamine-coated hard carbon powder.

[0089] Comparative Example 1

[0090] The same as Example 1, except that step (4) and step (5) are not performed, and the preliminary carbonized powder obtained in step (3) is the hard carbon material.

[0091] Comparative Example 2

[0092] The same as Example 1, except that the peach branches in step 1 are replaced with red willow branches.

[0093] Comparative Example 3

[0094] The same as Example 1, except that the peach branches in step 1 are replaced with camellia branches.

[0095] Comparative Example 4

[0096] (1) 5 g of peach branches were selected, crushed and sieved (200 mesh) in a grinder, washed and dried to obtain a biomass precursor.

[0097] (2) The biomass precursor was pre-oxidized in an air atmosphere (temperature of 300°C, holding time of 2h) to obtain a pre-oxidized sample.

[0098] (3) 0.3 g of the pre-oxidized sample and 0.05 g of dopamine hydrochloride (mass ratio of 6:1) were dispersed in 40 mL of Tris buffer, fully reacted for 24 h, filtered, washed and dried to obtain a polydopamine-coated pre-oxidized powder.

[0099] (4) The polydopamine-coated pre-oxidized powder was subjected to high-temperature carbonization treatment (carbonization temperature was 900°C and insulation time was 2 h) under N2 atmosphere to obtain a surface-optimized biomass hard carbon material.

[0100] Application Example 1

[0101] Preparation of sodium ion battery negative electrode:

[0102] (1) Dissolve 0.09 g of the hard carbon material prepared in the embodiment or the comparative example and 0.01 g of sodium alginate (the mass ratio of the hard carbon material to sodium alginate is 9:1) in deionized water to obtain an electrode slurry; use a 150 μm thick scraper to evenly apply the obtained electrode slurry on an aluminum current collector, dry it, and then punch it on a tablet press to obtain a sodium ion battery negative electrode sheet with a diameter of 11 mm.

[0103] (2) The sodium ion battery negative electrode sheet prepared in step (1) was placed on the positive electrode side of the half-cell, the metal sodium sheet was used as the counter electrode, the electrolyte was a commercially available sodium ion electrolyte, and the diaphragm was a GF / D diaphragm. The button cells were assembled under an argon atmosphere and the electrochemical performance was tested. The voltage range was 0.01 to 3.0 V. The results are shown in Tables 1 and Figures 4 to 6 .

[0104] Figure 4 The first cycle charge and discharge curve of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention (HC@PDAC is a biomass hard carbon material with a surface coated with a polydopamine-derived carbon layer, i.e., the surface-optimized biomass hard carbon material prepared in Example 1); Figure 5 This is a rate performance diagram of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention;

[0105] Figure 6 This is a cycle performance diagram of a sodium ion battery prepared using the surface-optimized biomass hard carbon material prepared in Example 1 of the present invention.

[0106] Depend on Figure 4 It can be seen that the biomass hard carbon material prepared in Example 1 has a first reversible specific capacity of 364 mAh / g and a high first coulombic efficiency of 89% at a current density of 0.1C (1C = 300 mA / g). It also has high first coulombic efficiency and high reversible specific capacity. This comprehensive performance is better than most of the biomass hard carbon negative electrodes reported in the prior art. In addition, Figure 5 It can be seen that the surface-optimized biomass hard carbon anode prepared in Example 1 also has excellent rate performance, and still has a specific capacity of more than 100 mAh / g at a high current density of 10C (10C = 3000 mA / g); Figure 6 It can be seen that the material also has excellent cycle stability, and the capacity retention rate is still above 90% after 200 cycles.

[0107] Table 1 Electrochemical performance

[0108]

[0109]

[0110] As can be seen from Table 1, the use of the surface-optimized biomass hard carbon material prepared by the present invention as the negative electrode of the sodium ion battery can obtain excellent first coulombic efficiency and reversible specific capacity, indicating that the embodiment after appropriate dopamine surface optimization effectively reduces the defects on the material surface, optimizes the surface functional groups, and improves the sodium storage performance.

[0111] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing biomass hard carbon, characterized in that: The following steps are involved: (1) pre-oxidizing the biomass raw material and then carbonizing it at high temperature under an inert atmosphere to obtain a preliminary carbonized powder; (2) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution to obtain a polydopamine-coated hard carbon powder after reaction; (3) Carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain the biomass hard carbon.

2. The preparation method according to claim 1, characterized in that: In step (1): The pre-oxidation temperature is 200-500°C and the holding time is 2-10h; And / or, the high temperature carbonization temperature is 1300-1500° C., and the time is 2-4 hours.

3. The preparation method according to claim 1, characterized in that: In step (2): the mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:

1.

4. The preparation method according to claim 1, characterized in that: In step (3): the temperature of the high temperature carbonization is 900-1100° C. and the time is 2-4 hours.

5. A biomass hard carbon prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the biomass hard carbon according to claim 5 in the preparation of sodium ion batteries.

7. A sodium ion battery negative electrode, characterized in that: Including the biomass hard carbon as described in claim 5.

8. A method for optimizing the surface of biomass hard carbon, characterized in that: The following steps are involved: (1) pre-oxidizing the biomass raw material and then carbonizing it at high temperature under an inert atmosphere to obtain a preliminary carbonized powder; (2) dispersing the preliminary carbonized powder and dopamine hydrochloride in a buffer solution to obtain a polydopamine-coated hard carbon powder after reaction; (3) Carbonizing the polydopamine-coated hard carbon powder at high temperature under an inert atmosphere to obtain the biomass hard carbon.

9. The biomass hard carbon surface optimization method according to claim 8, characterized in that: In step (1), the pre-oxidation temperature is 200 to 500° C. and the holding time is 2 to 10 hours; And / or, step (1): the temperature of the high temperature carbonization is 1300-1500° C., and the time is 2-4 hours; And / or, step (2): the mass ratio of the preliminary carbonized powder to dopamine hydrochloride is 5:1 to 10:1; And / or, in step (3): the temperature of the high temperature carbonization is 900-1100° C., and the time is 2-4 hours.

Citation Information

Cited By

  • Biomass-based sodium-ion battery hard carbon materials, their preparation methods and applications

    CN120664526B